Photoactivated miR-148b–nanoparticle conjugates improve closure of critical size mouse calvarial defects. (15th January 2015) - Qureshi, Ammar T.; Doyle, Andrew; Chen, Cong; Coulon, Diana; Dasa, Vinod; Del Piero, Fabio; Levi, Benjamin; Monroe, W. Todd; Gimble, Jeffrey M.; Hayes, Daniel J.
Graphical abstract: Abstract: Inducible systems providing temporal control of differentiation have the potential to improve outcomes in surgical reconstruction and regenerative medicine by precise modulation of wound healing and tissue repair processes. The aim of this study was to demonstrate that nanoformulated microRNA (miRNA) conjugates activated via photo exposure can lead to the induced osteogenic differentiation of human adipose-derived stromal/stem cells (hASCs) in vivo. The conjugate PC-miR-148b–SNP, a mimic of miRNA-148b tethered to silver nanoparticles (SNPs) via a photolabile linker, was used to modulate gene expression for improved closure of a critical size defect drilled on the right parietal bone of male CD-1 nude homozygous mice. The PC-miR-148b–SNP conjugates added to hASCs and loaded to either Matrigel or polycaprolactone (PCL) scaffolds resulted in different levels of healing of the defect. After 4 and 12 weeks, 3-D micro-computed tomography reconstructed images indicate statistically significant defect closure from 3.83 ± 1.19% to 5.46 ± 2.01% and 6.54 ± 4.28% to 32.53 ± 8.3% for non-photoactivated and photoactivated conjugates, respectively, in the PCL scaffolds. The results were confirmed with H&E and Masson's Trichrome stains in the transverse sections of photoactivated conjugates. Collagen fiber staining was greatest at 12 weeks when it reached approximately the same density and thickness as the native calvarium. This technology provides a platform that can be used with other miRNAs that actively govern the pathways responsible for regenerative and wound healing processes.